2013
DOI: 10.3762/bjoc.9.40
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Diels–Alder reaction with >C=P– functionality of the 2-phosphaindolizine-η1-P-aluminium(O-menthoxy) dichloride complex: experimental and theoretical results

Abstract: SummaryThe Diels–Alder reaction of the 2-phosphaindolizine-η1-P-aluminium(O-menthoxy) dichloride complex with dimethylbutadiene was investigated experimentally and computationally. The >C=P– functionality of the complex reacts with 2,3-dimethylbutadiene with complete diastereoselectivity to afford [2 + 4] cycloadducts. Calculation of the model substrate, 3-methoxycarbonyl-1-methyl-2-phosphaindolizine-P-aluminium(O-menthoxy) dichloride (7a), at the DFT (B3LYP/6-31+G*) level reveals that the O-menthoxy moiety bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 50 publications
3
11
0
Order By: Relevance
“…In accordance with the theoretical results, DA reaction of 2-phosphaindolizines ( 47 ) could be accomplished with complete diastereoselectivity, as indicated by 31 P NMR, with a single product being formed in each case ( Scheme 13 ) [ 40 ].…”
Section: Reactions Responsesupporting
confidence: 74%
See 1 more Smart Citation
“…In accordance with the theoretical results, DA reaction of 2-phosphaindolizines ( 47 ) could be accomplished with complete diastereoselectivity, as indicated by 31 P NMR, with a single product being formed in each case ( Scheme 13 ) [ 40 ].…”
Section: Reactions Responsesupporting
confidence: 74%
“…The successful results described above motivated us to investigate asymmetric DA reaction across the >C=P- moiety of 2-phosphaindolizines by using a chiral organoaluminium catalyst, namely, o-menthoxyaluminium dichloride [ 40 ].…”
Section: Reactions Responsementioning
confidence: 99%
“…This can be understood in terms of the weaker allylic CH bond (in propene) compared with common sp 3 CH bonds (in propane), 78.4 vs. 100.1 kcal mol −1 10. The discovery of InCl 2 + as the real catalyst is helpful for understanding the present cycloisomerization of 1,6‐enynes and other In(III),11ac Al(III)6d and Bi(III)11d catalyzed reactions as well.…”
Section: Methodsmentioning
confidence: 99%
“…We subsequently accomplished the DA reaction of a 2-phosphaindolizine-η 1 -P-aluminum(O-menthoxy)dichloride complex with DMB in which the [2+4]cycloadducts were obtained with complete diastereoselectivity (Scheme 10). 31 Computational calculations revealed that the O-menthoxy moiety blocked the Re face of the >C=Pfunctionality directing the diene to attack from the Si face exclusively. 31…”
Section: Organo-aluminum Chloride Catalyzed Diels-alder Reactions Of 2-phosphaindolizinesmentioning
confidence: 99%
“…31 Computational calculations revealed that the O-menthoxy moiety blocked the Re face of the >C=Pfunctionality directing the diene to attack from the Si face exclusively. 31…”
Section: Organo-aluminum Chloride Catalyzed Diels-alder Reactions Of 2-phosphaindolizinesmentioning
confidence: 99%